Magnetic and transport properties of La0.8Sr0.2MnO3/La0.8Ca0.2MnO3 bilayer - Prokhorov, V.G.; Kaminsky, G.G.; Komashko, V.A.; Lee, Y.P.; Park, J.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The effects of lattice strain on the magnetic and the transport properties of La0.8Sr0.2MnO3 films grown on an (001) LaAlO3 substrate and on a La0.8Ca0.2 MnO3 layer were studied. It was observed that the metal-insulator and the ferromagnetic transitions occur at higher temperatures for the film deposited on La0.8Ca0.2 MnO3 layer than on LaAlO3. The dependence of Curie temperature on the bulk and the Jahn-Teller strains were also determined.